The Effect of Renting in Cropland on Livelihood Choices and Agricultural Commercialization: A Case Study from Rural Vietnam - Oliver Schulte; Trung Thanh Nguyen; Ulrike Grote (The European Journal of Development Research, 2022)
This paper investigates the role of land rental markets in livelihood choices using data from 792 farming households in rural Vietnam. First, we cluster households according to livelihood strategies and estimate the determinants of the respective decision. In a second step, we analyze the contribution of rented land in linking smallholders to output markets. Our results suggest that rented land can provide smallholders with an opportunity to increase their agricultural activities and avoid resorting to less remunerative activities such as agricultural wage labor. Moreover, rented crop area increases the probability of market participation as well as the quantity of sales. Our results point to the need for a further liberalization of land rental markets specifically targeted at households that have been excluded from more remunerative livelihood strategies previously. Supporting these households to have access to the assets required to cultivate the additional area is thus recommended.
Keywords: 330; Livelihoods; Commercialization; Control function; Double-Hurdle; Land markets